Retrospective study of parasitic diseases of cattle through laboratory analysis of clinical samples at Bangladesh Livestock Research Institute, Regional Station, Baghabari, Sirajganj, Bangladesh - Kabir, Md Humayun; Ershaduzzaman, Md; Islam, Mohammed Sirajul; Rahman, Seikh Masudur; Karim, Md Rezaul; Hasan, Md Zakir; Miah, Md Abu Haris; Ali, Md Yousuf; Mahjabun, Shafaat; Aktar, Sumona; Shahjahan, Md (Asian Journal of Medical and Biological Research, 2018)
a